Literatura (d)e resistência: o grito aguerrido de escritores quare - Morais, Fernando Luís de [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Numa sociedade intransigente, que relega ao limbo os indivíduos cujas identidades raciais/étnicas, de gênero e de classe distanciam-se dos ditames preconizados pelo hegemônico padrão eurocêntrico, cis-heterossexual, de classe média/alta, afirmar-se negro-gay-pobre, valorizando a própria identidade, constitui um processo de resistência e confronto em face da constante invisibilidade, obliteração e silenciamento. À vista disso, interessa-nos, nesta tese, perscrutar esses recintos a fim de investigar de que modo a interseccionalidade entabulada entre raça/etnia, gênero e classe em autores negros-gay (pobres) repercute em suas produções literárias, operando como manobra de insubordinação às inflexíveis diretrizes hegemônicas. A partir de uma triagem dos poemas de Thomas Grimes compilados nas antologias Poets on the Horizon: A Collection of Poetry (1988), Milking Black Bull: 11 Gay Black Poets (1995) e em seu livro Reclamations (1994), da produção poética de Waldo Motta nos livros Eis o homem (1987) e Bundo e outros poemas (1996), e também dos escritos que compõem a coletânea In the Life: A Black Gay Anthology ([1986] 2008), buscaremos desbravar leituras que indiciem como os sujeitos negros-gay-pobres foram – e ainda têm sido – subjugados ao anonimato e invisibilizados não só enquanto escritores mas enquanto sujeitos sociais e políticos. Sustentamos que essas produções escritas atuam como um arsenal de instrumentos de denúncia das discriminações sociais e da precária posição ocupada por sujeitos negros-gay de classe baixa num reduto marcado pelos parâmetros da branquidade, da heterossexualidade e do classismo. As reflexões aqui construídas estão em consonância com as analíticas queer e quare. O aporte crítico-teórico sobre o qual se sustenta este trabalho abrange obras como as de Almeida (2018), Butler (2014, 2016, 2018, 2019), Campbell e Kean (1997), Collins e Bilge (2016), Crenshaw (1995), Hall (2003), Johnson (2005), Lorde (2007, 2019), Restier e Souza (2019) e Wilchins (2004).

In an uncompromising society which relegates to limbo individuals whose race/ethnic, gender, class identities deviate from the dictates advocated by the hegemonic Eurocentric, cis-heterosexual, middle/upper-class pattern, asserting oneself as a Black gay poor male, proud of one’s identity, constitutes a process of resistance and confrontation in the face of continual invisibility, obliteration and silencing. In view of this, this doctoral dissertation aims to peer into these zones in order to investigate how the intersectionality between race/ethnicity, gender and class in Black gay (poor) authors is reflected in their literary productions, operating as a maneuver of insubordination to the inflexible hegemonic directives. From a selection of poems of Thomas Grimes compiled in the anthologies Poets on the Horizon: A Collection of Poetry (1988), Milking Black Bull: 11 Gay Black Poets (1995) and in his book Reclamations (1994), from the poetic production of Waldo Motta in the books Eis o homem (1987) and Bundo e outros poemas (1996), and also the writings that compose the collection In the Life: A Black Gay Anthology ([1986] 2008), we attempt to determine readings which indicate how Black gay poor subjects were – and still have been – subjected to anonymity and rendered invisible not only as writers but also socially and politically. We argue that such written productions serve as an arsenal of instruments for denouncing both social discrimination and the precarious position occupied by Black gay lower-class individuals in a stronghold marked by the parameters of whiteness, heterosexuality and classism. The reflections developed here are in line with Queer and Quare analytics. The theoretical framework under which this study is carried out is based mainly upon the contributions of Almeida (2018), Butler (2014, 2016, 2018, 2019), Campbell and Kean (1997), Collins and Bilge (2016), Crenshaw (1995), Hall (2003), Johnson (2005), Lorde (2007, 2019), Restier and Souza (2019) and Wilchins (2004).

Dans une société intransigeante qui relègue aux oubliettes les individus dont les identités de race/ethnie, de genre, de classe s’écartent des diktats préconisés par le modèle hégémonique eurocentrique, cis-hétérosexuel, de classe moyenne/supérieure, s’affirmer en tant qu’un homme noir-gay-pauvre, fier de son identité, constitue un processus de résistance et de confrontation face à l’invisibilité, à l’effacement continuel et à la mise en silence. Dans cette optique, cette thèse de doctorat vise à scruter ces zones afin d’étudier comment l’intersection entre la race/l’ethnie, le genre et la classe chez les auteurs gays-noirs (pauvres) se reflète dans leurs productions littéraires, opérant comme une manœuvre d’insubordination aux directives hégémoniques inflexibles. À partir d’une sélection de poèmes de Thomas Grimes compilés dans les anthologies Poets on the Horizon: A Collection of Poetry (1988), Milking Black Bull: 11 Gay Black Poets (1995) et dans son livre Reclamations (1994), de la production poétique de Waldo Motta dans les livres Eis o homem (1987) et Bundo e outros poemas (1996), ainsi que des écrits qui composent le recueil In the Life: A Black Gay Anthology ([1986] 2008), on essaie de déterminer les lectures qui indiquent comment les sujets gays-noirs pauvres ont été – et sont encore – soumis à l’anonymat et rendus invisibles non seulement en tant qu’écrivains mais aussi en tant que sujets sociaux et politiques. On soutient que ces productions écrites servent d’arsenal d’instruments pour dénoncer, à la fois, la discrimination sociale et la position précaire occupée par les hommes gays-noirs de la classe inférieure dans un bastion marqué par les paramètres de la blancheur, de l’hétérosexualité et du classisme. Les réflexions développées ici s’inscrivent dans la lignée de l’analytique queer et quare. Le cadre théorique dans lequel s’inscrit cette étude est principalement basé sur les contributions de Almeida (2018), Butler (2014, 2016, 2018, 2019), Campbell et Kean (1997), Collins et Bilge (2016), Crenshaw (1995), Hall (2003), Johnson (2005), Lorde (2007, 2019), Restier et Souza (2019) et Wilchins (2004).
Literature of/and resistance: the fearless cry of quare writers
Littérature de/et résistance : le cri intrépide des écrivains quare
Keywords: Identidade; Raça; Gênero; Classe; Interseccionalidade; Queer; Quare; Race; Gender; Class; Identities; Thomas Grimes; Waldo Motta